Exploring and Developing a New Culturally-Appropriate Diabetes Distress Scale in Taiwan - Ching-Ling Lin; Ching-Ling Lin; Ching-Ling Lin; Yao-Tsung Chang; Wen-Cheng Liu; Li-Chi Huang; Li-Chi Huang; Shin-Yi Tsao; Yu-Hsin Chen; Ruey-Yu Chen (Frontiers Media S.A., 2022)
IntroductionThe aim of this study was to develop and validate a new diabetes distress scale suitable for Chinese and Taiwanese culture.MethodsThis study collected the current diabetes distress measurement tools, re-organized current definitions about the domains of diabetes distress, and then developed a new tool. Three hundred and ninety-five participants from four hospitals in northern Taiwan were recruited by cluster randomized sampling for validity test.ResultsWe found the new diabetes distress scale had appropriate reliability and validity, including an acceptable model fit for the 12-item scale.ConclusionsThis new diabetes distress scale might be more directly related to emotional distress issues blood glucose control, improve the clinical conspicuity of diabetes distress, and even benefit the overall care of diabetic patients in Taiwan. Further studies about the validity and reliability of this new tool in a nationwide setting are needed.